2020
DOI: 10.1101/2020.04.29.20085498
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effective Heat Inactivation of SARS-CoV-2

Abstract: In this study, we aimed to evaluate the stability of SARS-CoV-2 under four different heat conditions (37, 42, 56, 60 °C) and report that the virus is stable at 37 °C for at least 24 hours. Heating at 56 °C for 30 minutes, however, effectively inactivated the virus while preserved the stability of viral RNA in both human sera and sputum samples. These findings provide critical information regarding the biology of the virus as well as a practical way to inactivate infectious virus that is potentially found in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
55
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(65 citation statements)
references
References 2 publications
9
55
1
Order By: Relevance
“…Among environmental surfaces specimens in our study, all positive specimens were collected within 3 days (≤3 days) after diagnosis. It means that without disinfection, the SARS-CoV-2 could survive on environmental surfaces for at least 3 days, and in other studies, the survival time was 0 to 14 days [33][34][35][36], which was consistent with current understanding. Therefore, enhance surfaces cleaning and disinfection were important and essential [20].…”
Section: Discussionsupporting
confidence: 82%
“…Among environmental surfaces specimens in our study, all positive specimens were collected within 3 days (≤3 days) after diagnosis. It means that without disinfection, the SARS-CoV-2 could survive on environmental surfaces for at least 3 days, and in other studies, the survival time was 0 to 14 days [33][34][35][36], which was consistent with current understanding. Therefore, enhance surfaces cleaning and disinfection were important and essential [20].…”
Section: Discussionsupporting
confidence: 82%
“…Indeed, heat treatment is often used to inactivate saliva patient samples, 29,30 thus conferring added biosafety by decreasing the likelihood of viral transmission via sample handling by personnel. Common conditions for SARS-CoV-2 inactivation are heating at 56-60°C for 30-60 min, 30,31 although other temperature and times have been examined. 30 Using intact, γirradiated SARS-CoV-2 spiked into fresh human saliva (that was confirmed to be SARS-CoV-2 negative), we observed dramatic time-and temperature-dependent improvement in SARS-CoV-2 detection by direct RT-qPCR, without the use of RNA extraction.…”
Section: Development Of a Direct Saliva-to-rt-qpcr Process For Detectmentioning
confidence: 99%
“…First, the time and duration of heating the saliva sample is critical. Standard protocols for heat inactivation of SARS-CoV-2 call for heating at ~60 o C for 30 minutes;30,31 while these conditions inactivate the virus, they do not allow for successful SARS-CoV-2 detection via direct RT-qPCR, likely because of the persistence of as-yet-unidentified factors in saliva that are inhibitory to RT-qPCR. Heating at 95°C for 30 minutes likely inactivates these inhibitory components and allows for excellent SARS-CoV-2 detection in this direct process that bypasses RNA isolation/purification.…”
mentioning
confidence: 99%
“…SARS‐CoV‐2 in virus transport medium (optimal conditions for virus survival) is highly stable at 4°C (< 0.7 log 10 reduction on day 14; Chin et al ., 2020). This is similar to experiments carried out with SARS‐CoV which demonstrated that the virus could survive for up to 14 days at 4°C in hospital wastewater, domestic sewage and dechlorinated tap water, but only persists for 2 days at 20°C (Wang et al ., 2020b). Similarly, a human coronavirus causing common cold (HCoV 229E) remained infectious for 10–100 days in tap water, yet for only 2–4 days in wastewater as determined by TCID 50 (tissue culture infectious dose 50% technique; Gundy et al ., 2008).…”
Section: Persistence Of Sars‐cov‐2mentioning
confidence: 99%
“…In virus transport medium, SARS‐CoV‐2 was inactivated after 5 min at 70°C (Chin et al ., 2020). In cell culture supernatant, the virus was inactivated in less than 30 and 15 min at 56°C and 65°C respectively (Wang et al ., 2020b). This set of data confirm that pasteurization will inactivate SARS‐CoV‐2 and substantiate the WHO statement that SARS‐COV‐2 is not more resistant to heat than the usual bacteria found in food.…”
Section: Sars‐cov‐2 Inactivation Technologiesmentioning
confidence: 99%